A nickel mesh-based anode molybdenum-manganese water electrolysis catalyst and preparation method thereof

By using an anode molybdenum manganese electrolytic water catalyst based on nickel net in the electrolytic water hydrogen production technology, the complexation reaction of potassium permanganate and molybdate is solved, and more efficient and stable hydrogen generation is achieved.

CN119776895APending Publication Date: 2025-04-08QINGQIJI ZHONGNENG (SUZHOU JIANGSU) HYDROGEN ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510059429.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the overpotential required for the reaction of the anode and anode and the resistance problems in the electrolytic water system lead to high actual voltage and high cost, and the use of precious metal material catalysts is not conducive to large-scale development.

Method used

The anode molybdenum manganese electrolytic catalyst based on nickel mesh is adopted to improve the specific surface area and active site of the catalyst through ultrasonic impregnation of potassium permanganate solution, and the electron conduction ability and activity of the catalyst are enhanced by the complexation reaction of molybdate.

Benefits of technology

It effectively reduces the reaction overpotential, improves the reaction rate, reduces production costs, and improves the stability and efficiency of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776895A_ABST
    Figure CN119776895A_ABST
Patent Text Reader

Abstract

The present invention discloses an anode molybdenum manganese electrolysis water catalyst based on nickel mesh and a preparation method thereof, comprising a plurality of steps such as pretreatment, potassium permanganate impregnation, and molybdate impregnation. Through the above-mentioned method, the present invention discloses an anode molybdenum manganese electrolysis water catalyst based on nickel mesh and a preparation method thereof, wherein potassium permanganate is used to increase the specific surface area of ​​the catalyst, increase the active point of the catalyst, and enter the nickel mesh carrier to form a heterogeneous doping structure, thereby effectively increasing the activity of the catalyst. At the same time, molybdate is used to form a molybdate complex during the impregnation process to be loaded on the surface of the electrode catalyst, thereby further increasing the number of active sites on the catalyst surface, improving the electronic conductivity and catalytic activity of the catalyst, reducing the reaction overpotential, increasing the reaction rate, and reducing the production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation and application of water electrolysis hydrogen evolution catalyst, and in particular to an anode molybdenum-manganese water electrolysis catalyst based on a nickel mesh and a preparation method thereof. Background Art

[0002] Compared with traditional fossil hydrogen production processes, water electrolysis hydrogen production technology can not only couple renewable energy, but also obtain hydrogen with high purity, low subsequent separation and purification costs, and no secondary pollution in the entire hydrogen production process. Therefore, it is considered to be a more ideal green hydrogen production method.

[0003] However, the current voltage of industrial water electrolysis is generally between 1.8 and 2.0 V, which has a lot of room for improvement compared to the theoretical bias potential of 1.23 V. In order to reduce the actual required voltage, it is necessary to solve the high overpotential required for the cathode and anode reactions and the resistance problems in the water electrolysis system. At present, precious metal materials represented by Pt are usually used as catalysts in the cathode hydrogen evolution reaction, and their high cost is not conducive to the large-scale development of hydrogen production by water electrolysis. Therefore, the development and research of efficient, stable, cheap, high-earth-content and large-scale synthesized hydrogen evolution electrocatalytic materials has important theoretical significance and practical value. Summary of the invention

[0004] In order to solve the above technical problems, a technical solution adopted by the present invention is: Provided is a method for preparing an anode molybdenum-manganese water electrolysis catalyst based on a nickel mesh, the steps comprising: (1) Immerse the nickel mesh in an alkaline solution to remove oil, take out the nickel mesh and rinse it with clean water, then place the nickel mesh in an acid cleaning solution and ultrasonically treat it at room temperature, take out the nickel mesh and continue to rinse it with clean water to complete the pretreatment; (2) preparing a potassium permanganate solution with a concentration of 0.1 M, immersing the pretreated nickel mesh in the potassium permanganate solution by a double immersion method, and then ultrasonicating at 30° C. for 0.5 h; then taking out the nickel mesh and placing it in a muffle furnace, and calcining it at a temperature of 350° C. for 1.5 h; (3) Prepare a complexing solution by mixing 100 ml of deionized water, 1.96-2.42 g of molybdate, 5 g of citric acid and 10 ml of 25% ammonia water, immerse the calcined nickel mesh in the complexing solution, stir thoroughly and then perform ultrasonic treatment. After the ultrasonic treatment, let it stand at room temperature for 12 hours and dry it at 80-100°C. (4) The dried mixture is placed in a muffle furnace and calcined at 350° C. for 4 h to obtain an anode electrode catalyst material with multiple active sites to be used as an anode for hydrogen production by water electrolysis.

[0005] In a preferred embodiment of the present invention, the nickel mesh is a nickel mesh woven from pure nickel wires sprayed with quartz sand on both sides.

[0006] In a preferred embodiment of the present invention, in step (1), the alkali solution is a sodium hydroxide solution with a concentration of 10%.

[0007] In a preferred embodiment of the present invention, in step (1), the degreasing temperature is 90° C. and the activation time is 1 hour.

[0008] In a preferred embodiment of the present invention, in step (1), the pickling solution is a hydrochloric acid solution with a concentration of 0.1 M.

[0009] In a preferred embodiment of the present invention, in step (1), the ultrasonic time during pickling is 30 minutes.

[0010] In a preferred embodiment of the present invention, in step (3), the molybdate includes sodium molybdate, ammonium molybdate, potassium molybdate or calcium molybdate.

[0011] In a preferred embodiment of the present invention, in step (3), the temperature during ultrasound is room temperature and the ultrasound time is 30 minutes.

[0012] In a preferred embodiment of the present invention, in steps (2) and (3), the ultrasonic power is 400W.

[0013] A nickel mesh-based anode molybdenum-manganese water electrolysis catalyst is prepared by any of the above methods and is used as an anode for electrolyzing water to produce hydrogen.

[0014] The beneficial effects of the present invention are as follows: potassium permanganate is used to increase the specific surface area of ​​the catalyst, increase the active points of the catalyst, and enter the nickel mesh carrier to form a heterogeneous doping structure, thereby effectively improving the activity of the catalyst; at the same time, molybdate is used to form a molybdate complex during the impregnation process to be loaded on the surface of the electrode catalyst, thereby further increasing the number of active sites on the catalyst surface, improving the electronic conductivity and catalytic activity of the catalyst, reducing the reaction overpotential, increasing the reaction rate, and reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which: Figure 1 is a metallographic microscope spectrum of the molybdenum-manganese water electrolysis catalyst obtained in Example 1 of the present invention; Figure 2 is the hydrogen evolution performance curve of the molybdenum-manganese water electrolysis catalyst obtained in Example 1 of the present invention; Figure 3It is the oxygen evolution performance curve of the molybdenum-manganese water electrolysis catalyst obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] See also Figure 1-3 , the embodiment of the present invention includes: An anode molybdenum-manganese water electrolysis catalyst based on a nickel mesh and a preparation method thereof, comprising the following steps: (1) Immerse the nickel mesh in alkaline solution for degreasing. Take out the nickel mesh and rinse it with clean water for 3 times. Then place the nickel mesh in an acid cleaning solution and ultrasonically treat it at room temperature. Take out the nickel mesh and continue to rinse it with clean water for 3 times to complete the pretreatment.

[0018] Further preferably, the nickel mesh is a nickel mesh woven from pure nickel wires sprayed with quartz sand on both sides.

[0019] More preferably, the alkali solution is a sodium hydroxide solution with a concentration of 10%, the degreasing temperature is 90° C., and the activation time is 1 hour.

[0020] Further preferably, the pickling solution is a 0.1 M hydrochloric acid solution, and the ultrasonic time during pickling is 30 min.

[0021] (2) Prepare a potassium permanganate solution with a concentration of 0.1 M, immerse the pretreated nickel mesh in it according to the double accumulation method, and then ultrasonicate it at 30°C for 0.5 h. Then, take out the nickel mesh and place it in a muffle furnace, and calcine it at 350°C for 1.5 h.

[0022] Furthermore, the ultrasonic power is 400W.

[0023] (3) Prepare a complex solution by mixing 100 ml of deionized water, 1.96-2.42 g of molybdate, 5 g of citric acid and 10 ml of 25% ammonia water. Immerse the calcined nickel mesh in the complex solution so that the concentration of molybdate in the complex solution is 0.1 M. Stir thoroughly and then perform ultrasonic treatment. After completion, let it stand at room temperature for 12 hours and dry it at 80-100°C.

[0024] Further preferably, the molybdate includes sodium molybdate, ammonium molybdate, potassium molybdate or calcium molybdate, and the temperature during the ultrasonic treatment is room temperature, and the ultrasonic time is 30 min.

[0025] (4) The dried mixture is placed in a muffle furnace and calcined at 350°C for 4 hours to obtain an anode electrode catalyst material with multiple active sites. Since this catalyst has better OER performance, it is used as the anode for hydrogen production by water electrolysis.

[0026] By using a woven nickel mesh with double-sided quartz sand sprayed as a substrate, the cost can be greatly controlled on the basis of ensuring that the electrode has good electrocatalytic hydrogen evolution performance. The active sites of the double-sided sandblasted electrocatalytic hydrogen evolution reaction are located at the edge of the exposed quartz sand and the nickel mesh. Therefore, potassium permanganate, a strong oxidant, can be used to add more active sites on the surface of the nickel mesh electrode catalyst to increase the specific surface area. After reacting with potassium permanganate, the activity and performance of the electrode catalyst can be better improved by impregnation with a complexing solution. Example

[0027] A double-sided sandblasted nickel mesh cut into 1*1cm was immersed in a 10% NaOH solution and heated at 90℃ for 1h in a water bath. After taking out the nickel mesh, it was rinsed with clean water 3 times, and then placed in a 0.1M hydrochloric acid solution, ultrasonicated at room temperature for 0.5h, and the nickel mesh was taken out and continued to be rinsed with clean water 3 times for use; 50ml of 0.1M potassium permanganate solution was prepared, and the nickel mesh was immersed in it according to the double accumulation method, and ultrasonicated at 30℃ for 0.5h; after taking out the nickel mesh, it was calcined at 350℃ for 1.5h; 100ml of deionized water, 2.42g of sodium molybdate, 5g of citric acid and 10ml of 25% ammonia water were prepared to prepare a complex solution, and then the treated nickel mesh was immersed in the complex solution, and ultrasonicated after sufficient stirring. After the ultrasonication ended, it was allowed to stand at room temperature for 12h, and then dried at 80℃, and finally calcined at 350℃ for 4h to obtain a composite molybdenum-manganese electrolytic water hydrogen evolution catalyst.

[0028] When testing, a three-electrode system was selected, using Hg / HgO as the reference electrode, a platinum electrode as the counter electrode, and a molybdenum-manganese electrolytic water hydrogen evolution catalyst as the working electrode. The current density of this catalyst under 1 mol / L KOH conditions was 300 mA / cm 2 The overpotential for hydrogen evolution is 635 mV and the overpotential for oxygen evolution is 724 mV. Example

[0029] A double-sided sandblasted nickel mesh cut into 1*1cm was immersed in a 10% NaOH solution and heated at 90℃ for 1h. After taking out the nickel mesh, it was rinsed with clean water for 3 times, and then placed in a 0.1M hydrochloric acid solution for ultrasonic treatment at room temperature for 0.5h. The nickel mesh was taken out and continued to be rinsed with clean water for 3 times for standby; 50ml of 0.1M potassium permanganate solution was prepared, and the nickel mesh was immersed in it according to the double accumulation method, and then ultrasonicated at 30℃ for 0.5h. After taking out the nickel mesh, the nickel mesh was calcined at a temperature of 350℃ for 1.5h; 100ml of deionized water, 1.96g of ammonium molybdate, 5g of citric acid and 10ml of 25% ammonia water were prepared to prepare a complex solution, and then the treated nickel mesh was immersed in the complex solution, and ultrasonic treatment was performed after sufficient stirring. After the ultrasonic treatment, it was allowed to stand at room temperature for 12h, and then dried at 80℃, and finally calcined at a temperature of 350℃ for 4h to obtain a composite molybdenum-manganese hydrogen evolution electrode catalyst material.

[0030] When testing, a three-electrode system was selected, using Hg / HgO as the reference electrode, a platinum electrode as the counter electrode, and a molybdenum-manganese electrolytic water hydrogen evolution catalyst as the working electrode. The current density of this catalyst under 1 mol / L KOH conditions was 300 mA / cm 2 The overpotential for hydrogen evolution is 612 mV and the overpotential for oxygen evolution is 758 mV. Example

[0031] A double-sided sandblasted nickel mesh cut into 1*1cm was immersed in a 10% NaOH solution and heated at 90℃ for 1h. After taking out the nickel mesh, it was rinsed with clean water for 3 times, and then placed in a 0.1M hydrochloric acid solution for ultrasonic treatment at room temperature for 0.5h. The nickel mesh was taken out and continued to be rinsed with clean water for 3 times for use; 50ml of 0.1M potassium permanganate solution was prepared, and the nickel mesh was immersed in it according to the double accumulation method, and then ultrasonicated at 30℃ for 0.5h, and the nickel mesh was taken out and calcined at 350℃ for 1.5h; 100ml of deionized water, 2.38g of potassium molybdate, 5g of citric acid and 10ml of 25% ammonia water were prepared to prepare a complex solution, and then the treated nickel mesh was immersed in the above complex solution, and ultrasonic treatment was performed after sufficient stirring. After the ultrasonic treatment, it was allowed to stand at room temperature for 12h, and dried at 100℃, and finally calcined at 350℃ for 4h to obtain a composite molybdenum-manganese hydrogen evolution electrode catalyst material.

[0032] When testing, a three-electrode system was selected, using Hg / HgO as the reference electrode, a platinum electrode as the counter electrode, and a molybdenum-manganese electrolytic water hydrogen evolution catalyst as the working electrode. The current density of this catalyst under 1 mol / L KOH conditions was 300 mA / cm 2 The overpotential for hydrogen evolution is 644 mV and the overpotential for oxygen evolution is 782 mV. Example

[0033] A double-sided sandblasted nickel mesh cut into 1*1cm was immersed in a 10% NaOH solution and heated at 90℃ for 1h. After taking out the nickel mesh, it was rinsed with clean water for 3 times, and then placed in a 0.1M hydrochloric acid solution for ultrasonic treatment at room temperature for 0.5h. The nickel mesh was taken out and continued to be rinsed with clean water for 3 times for use; 50ml of 0.1M potassium permanganate solution was prepared, and the nickel mesh was immersed in it according to the double accumulation method, and then ultrasonicated at 30℃ for 0.5h, and the nickel mesh was taken out and calcined at a temperature of 350℃ for 1.5h; 100ml of deionized water, 2.00g of calcium molybdate, 5g of citric acid and 10ml of 25% ammonia water were prepared to prepare a complex solution, and then the treated nickel mesh was immersed in the above complex solution, and ultrasonic treatment was performed after sufficient stirring. After the ultrasonic treatment, it was allowed to stand at room temperature for 12h, and dried at 100℃, and finally calcined at a temperature of 350℃ for 4h to obtain a composite molybdenum-manganese hydrogen evolution electrode catalyst material.

[0034] When testing, a three-electrode system was selected, using Hg / HgO as the reference electrode, a platinum electrode as the counter electrode, and a molybdenum-manganese electrolytic water hydrogen evolution catalyst as the working electrode. The current density of this catalyst under 1 mol / L KOH conditions was 300 mA / cm 2 The overpotential for hydrogen evolution is 613 mV and the overpotential for oxygen evolution is 772 mV.

[0035] The beneficial effects of the nickel mesh-based anode molybdenum-manganese water electrolysis catalyst and the preparation method thereof of the present invention are: 1. A water electrolysis hydrogen evolution catalyst with multiple active sites is prepared by ultrasonic impregnation of potassium permanganate solution. On the one hand, since the raw materials for preparing the catalyst are widely available and inexpensive, the production cost can be greatly reduced; on the other hand, potassium permanganate can play a certain pore-forming role in the catalyst preparation process to increase the specific surface area of ​​the catalyst material, thereby increasing the active point of the catalyst and improving the catalytic activity of the catalyst. In addition, the potassium permanganate solution can be used again after being recovered, which can further control the cost; 2. Using the strong oxidizing property of potassium permanganate, a series of redox reactions occur on the surface of the nickel mesh to generate MnO2. After the reaction, part of the excess potassium permanganate will enter the nickel mesh carrier to form a heterogeneous doping structure, which can effectively improve the activity of the catalyst; 3. During the impregnation process, molybdate will undergo a complex reaction with itself to form a molybdate complex to be loaded on the surface of the electrode catalyst, thereby increasing the number of active sites on the catalyst surface. At the same time, the introduction of molybdenum elements can improve the catalyst's electronic conductivity and catalytic activity, reduce the reaction overpotential, and increase the reaction rate.

[0036] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a nickel mesh-based anode molybdenum-manganese electrolytic water catalyst, characterized in that the steps include: (1) Immerse the nickel mesh in an alkaline solution to remove oil, take out the nickel mesh and rinse it with clean water, then place the nickel mesh in an acid cleaning solution and ultrasonically treat it at room temperature, take out the nickel mesh and continue to rinse it with clean water to complete the pretreatment; (2) preparing a potassium permanganate solution with a concentration of 0.1 M, immersing the pretreated nickel mesh in the potassium permanganate solution by a double immersion method, and then ultrasonicating at 30° C. for 0.5 h; then taking out the nickel mesh and placing it in a muffle furnace, and calcining it at a temperature of 350° C. for 1.5 h; (3) Prepare a complexing solution by mixing 100 ml of deionized water, 1.96-2.42 g of molybdate, 5 g of citric acid and 10 ml of 25% ammonia water, immerse the calcined nickel mesh in the complexing solution, stir thoroughly and then perform ultrasonic treatment. After the ultrasonic treatment, let it stand at room temperature for 12 hours and dry it at 80-100°C. (4) The dried mixture is placed in a muffle furnace and calcined at 350° C. for 4 h to obtain an anode electrode catalyst material with multiple active sites to be used as an anode for hydrogen production by water electrolysis.

2. The method for preparing a nickel mesh-based anode molybdenum-manganese water electrolysis catalyst according to claim 1, characterized in that: The nickel mesh is a nickel mesh woven from pure nickel wires sprayed with quartz sand on both sides.

3. The method for preparing a nickel mesh-based anode molybdenum-manganese water electrolysis catalyst according to claim 1, characterized in that: In step (1), the alkali solution is a sodium hydroxide solution with a concentration of 10%.

4. The method for preparing a nickel mesh-based anode molybdenum-manganese water electrolysis catalyst according to claim 1, characterized in that: In step (1), the degreasing temperature is 90°C and the activation time is 1 hour.

5. The method for preparing a nickel mesh-based anode molybdenum-manganese water electrolysis catalyst according to claim 1, characterized in that: In step (1), the pickling solution is a hydrochloric acid solution with a concentration of 0.1 M.

6. The method for preparing a nickel mesh-based anode molybdenum-manganese water electrolysis catalyst according to claim 1, characterized in that: In step (1), the ultrasonic time during pickling is 30 minutes.

7. The method for preparing a nickel mesh-based anode molybdenum-manganese water electrolysis catalyst according to claim 1, characterized in that: In step (3), the molybdate includes sodium molybdate, ammonium molybdate, potassium molybdate or calcium molybdate.

8. The method for preparing a nickel mesh-based anode molybdenum-manganese water electrolysis catalyst according to claim 1, characterized in that: In step (3), the temperature during ultrasound is room temperature and the ultrasound time is 30 min.

9. The method for preparing a nickel mesh-based anode molybdenum-manganese water electrolysis catalyst according to claim 1, characterized in that: In steps (2) and (3), the ultrasonic power is 400W.

10. An anode molybdenum-manganese water electrolysis catalyst based on nickel mesh, characterized in that: Prepared by any method of claims 1-9, used as an anode for producing hydrogen by electrolysis of water.